La hyper_calle : la extrusión de San Victorino (2020)
In the heart of Bogota, a city of limits, in which it is increasingly common to drive people away from the streets, there?s a place that stands out for doing absolutely the opposite: San Victorino is a commercial cluster within this immense city in which the imposition of its own rules take over the entire space. Tides of vendors, buyers, commuters and visitors invade the surface. The architecture suddenly blurs behind layers of products and merchandise. The hyper_street takes these elements that synthetize the essence of San Victorino and extrudes them through space and time, allowing the commercial activity, that is currently completely dependent on the activity of the ground floor and its time slots, to link the upper floors, attract new actors and inhabit the public space in the different temporal scales and scenarios.